Abuse of Cryptocurrency to Funding International Terrorism Activities - Wardhana, Andhika Tegar; Nugroho, Bambang Wahyu (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Terrorist organizations began to adjust themselves with the development of information and communications technology, especially in their efforts to finance their activities. Cryptocurrency is one of the latest advancement in financial technologies which is potentially support their actions. Even, it has already actualized in some cases. This research aims to examine what underlies terrorist organizations to start using cryptocurrency and to find forms of its recent activities and its further possibilities. This research uses qualitative approach through examining some sample cases and tries to extrapolate it into larger phenomena. The data obtained in the form of secondary data, namely data from books, articles, academic papers, journals, news, as well as electronic media. This research applies the theory of international crime to frame that terrorist organizations are illegal entities, theory of disruptive technology to describe the nature of cryptocurrency as a new form cyber-based financial technology, and theory of the diffusion of innovation to explain why in the recent internet era, cryptocurrency has a large potential to attract financial investments globally. This work found that terrorist organizations has been starting to use cryptocurrency to finance their activities based on its anonymous and less-regulated natures, both are delivering a new challenge of cybercrimes beyond the conventional scrutiny in finance and banking transfer, as well as counterattacks toward money counterfeit and money laundering.